Testing woodchips for their efficiency in stimulating aquatic nutrient uptake at different experimental and spatial scales - Akbari, Elmira; Matjašič, Tjaša; Dittrich, Anna-Lisa; Attermeyer, Katrin; Hood-Nowotny, Rebecca; Weigelhofer, Gabriele (Frontiers in Environmental Science, 2024)
Woodchips as a source of particulate organic carbon (POC) are proposed as a nature-based solution to enhance nutrient uptake and retention in agricultural streams. However, the effective implementation of woodchips for nutrient removal in streams requires an advanced understanding of their potential and limits, considering their performance under various environmental conditions. This study tested the efficiency of woodchips on the uptake of soluble reactive phosphorus (SRP) and ammonium (N-NH4) across different experimental scales and complexity. We investigated whether the presence of woodchips can increase SRP and N-NH4 uptake in laboratory flumes under controlled conditions, outdoor flumes under semi-controlled conditions, and agricultural streams. Additionally, we examined how the effects of woodchips will change over time via a 6-week incubation in the outdoor flumes. The woodchips were pre-colonized for four weeks to allow the growth of biofilms. We performed short-term nutrient additions without (control) and with (treatment) woodchips in all three experimental setups. Uptake parameters were determined via concentration changes over time in the laboratory flumes and concentration changes over travel distance in the outdoor flumes and the stream channels. The effects of woodchips on SRP and N-NH4 uptake rates were analyzed using an effect size model. We found positive effects of woodchips on nutrient uptake only in the laboratory flumes but no or even negative effects in the outdoor flumes and the agricultural streams. Over the 6-week incubation in the outdoor flumes, we did not observe significant changes in the effects of woodchips on nutrient uptake. These findings highlight that considering experimental scales and influencing environmental conditions is crucial when testing the application of woodchips as nature-based solutions to mitigate nutrient loads in agricultural streams.